Environmental accounting practices and cost of capital of enterprises in Vietnam - Nguyen Huu Anh; Nguyen La Soa; Ha Hong Hanh (Cogent Economics & Finance, 2020)
This study aimed to investigate the nexus between the level of environmental financial accounting practices (EFAP) and cost of capital. The population of this study is 1.188 firm-year observations. However, we excluded 408 firm-year with less than 2 years of information to calculate EFAP, 73 firm-year without sufficient financial accounting information to calculate the cost of capital and 35 firm-year without sufficient financial accounting information to calculate control variables. Finally, this paper used a sample of 672 firm-year observations of listed companies on the Vietnam stock market for 5 years from 2013 to 2017. Two-stage regressions with the lag term are adopted to address econometric issues and to improve the accuracy of the regression coefficients. The results show that Vietnamese firms with higher EFAP performance can rapidly reduce their cost of capital. The findings also indicate that capital structure does not play a moderating role to evaluate the relationship between EFAP and the cost of capital.
Keywords: M41; M42; M48; 330; accounting information; capital structure; cost of capital; environment accounting; environmental financial accounting practices